2009
DOI: 10.1098/rstb.2009.0156
|View full text |Cite
|
Sign up to set email alerts
|

Sola schola et sanitate: human capital as the root cause and priority for international development?

Abstract: This paper summarizes new scientific evidence supporting the hypothesis that among the many factors contributing to international development, the combination of education and health stands out as a root cause on which other dimensions of development depend. Much of this recent analysis is based on new reconstructions and projections of populations by age, sex and four levels of educational attainment for more than 120 countries using the demographic method of multi-state population dynamics. It also refers to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 26 publications
1
24
0
6
Order By: Relevance
“…It is worth noting that future decline in Africa is far from being a certainty and that, in analogy to the above described 'Low Fertility Trap', there may be a high fertility trap mechanism in which rapid population growth inhibits the development that would bring down fertility (Dasgupta 1993;King 1990). Past experience has shown that the best way to break this vicious circle is the combination of female education with provision of family planning services (see, for example, Bongaarts and Sinding 2011;Lutz 2009;and Jejeebhoy 1996).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that future decline in Africa is far from being a certainty and that, in analogy to the above described 'Low Fertility Trap', there may be a high fertility trap mechanism in which rapid population growth inhibits the development that would bring down fertility (Dasgupta 1993;King 1990). Past experience has shown that the best way to break this vicious circle is the combination of female education with provision of family planning services (see, for example, Bongaarts and Sinding 2011;Lutz 2009;and Jejeebhoy 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Although human population reduction will not immediately solve environmental problems (Bradshaw and Brook 2014), if actively tackled, it has the potential to deliver important long-term sustainability (Bradshaw and Brook 2014) The goals address reproductive (Target 3.7) and universal (Target 3.8) health care as well as drivers of decreased fertility such as family planning (Bongaarts and Sinding 2011) (Target 3.7), the empowerment of women (Lutz 2009, McCrary andRoyer 2011) (SDG 5), and education (Skirbekk 2008, Lutz 2009, Bradshaw and Brook 2014 (SDGs 3, 4). However, although a decrease in per capita fertility has been observed over the last few decades (see Bradshaw and Brook 2014), the global human population is unlikely to stabilize this century (Gerland et al 2014).…”
Section: Intergenerational and Population Concernsmentioning
confidence: 99%
“…This human capital index is interesting in the perspective that it also combines education and intellectual quotient (IQ). Hence, it takes both the input and output dimensions of human capital into account, which is not the case with traditional indicators (Lutz, 2009). Our econometric results show a solid statistical linkage between genetic distance and intelligence.…”
Section: Introductionmentioning
confidence: 99%